2012
DOI: 10.1371/journal.pone.0044504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Fertilizer Application on the Soil Fertility of Paddy Soils in Red Soil Region of Southern China

Abstract: Appropriate fertilizer application is an important management practice to improve soil fertility and quality in the red soil regions of China. In the present study, we examined the effects of five fertilization treatments [these were: no fertilizer (CK), rice straw return (SR), chemical fertilizer (NPK), organic manure (OM) and green manure (GM)] on soil pH, soil organic carbon (SOC), total nitrogen (TN), C/N ratio and available nutrients (AN, AP and AK) contents in the plowed layer (0–20 cm) of paddy soil fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
80
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(96 citation statements)
references
References 48 publications
12
80
1
2
Order By: Relevance
“…Results from our previous long-term monitoring suggest that swine manure and mineral fertilizer may increase soil acidity (Dong et al, 2012), which is in agreement with Steiner et al (2007). The positive relationships between soil pH and TP contents in this study confirmed that calcium-magnesium phosphate fertilizers could neutralize acidity in acid soils (Fig.…”
Section: Effects Of Fertilizer Practices On Soil Propertiessupporting
confidence: 89%
See 4 more Smart Citations
“…Results from our previous long-term monitoring suggest that swine manure and mineral fertilizer may increase soil acidity (Dong et al, 2012), which is in agreement with Steiner et al (2007). The positive relationships between soil pH and TP contents in this study confirmed that calcium-magnesium phosphate fertilizers could neutralize acidity in acid soils (Fig.…”
Section: Effects Of Fertilizer Practices On Soil Propertiessupporting
confidence: 89%
“…Based on similar amounts of P fertilizer, manure fertilizer contributed more to soil TP contents than the mineral fertilizer (Table 2). This is in agreement with long-term results from paddy soil trials (Dong et al, 2012;Wang et al, 2012). Organic manure contains a large amount of organic P, which will be released slowly, and will be beneficial to soil quality and crops over the longterm (Bi et al, 2009).…”
Section: Effects Of Fertilizer Practices On Soil Propertiessupporting
confidence: 87%
See 3 more Smart Citations